Purpose for Elijah and Elisha in the Books of Kings - Hess, Richard S. (Tyndale bulletin, 2023)
The study of 1 and 2 Kings often assumes that the division between the two books was an arbitrary one that was made about halfway between the beginning and end of the text of Kings. The investigation of this question reveals not only a rationale behind the division between the two ‘books’; it also raises the larger question of the contrasting roles played by the kings who begin and end the text, and by the prophets whose central role in the books provides hope and life. By tracing major narrative arcs across the beginning and end of 1 and 2 Kings as well as across the appearances and departures of Elijah and Elisha, the themes of physical death and spiritual life set a dramatic tone in the pages of these accounts and provide hope in the midst of judgement.